Languaging-for-learning: Legitimising translanguaging and enabling multimodal practices in third spaces. Issue 3 (30th September 2016) - Guzula, Xolisa; McKinney, Carolyn; Tyler, Robyn
Abstract: While there have been significant paradigm shifts in conceptualising language in applied linguistics and in critiquing the historical monolingual bias in the discipline, monolingual approaches continue to dominate officially prescribed language teaching and learning approaches, curricula, policy and materials in South African education. In this paper we argue that monolingual ideologies have negative consequences for the positioning of South African learners as well as for their participation in the curriculum. We focus on how learner capacities are enabled when a heteroglossic and multimodal orientation to language practices and meaning-making is taken up. We explore processes of languaging-for-learning in two established third spaces—the first, an after-school literacy club for Grades 3–6 learners in Khayelitsha, Cape Town, and the second, a mathematics holiday programme for Grade 11 students in the rural Eastern Cape. We argue that our cases show how it is possible to bridge the gap between heteroglossic conceptions of language and languaging in applied linguistics, and what is conceived as legitimate language practices in the classroom. We conclude that the translanguaging and multimodal strategies in the two cases offer new pedagogical strategies for meaning-making that challenge the dominant monolingual orientation to children's languaging in many classrooms.